The People's Health (Newcastle-on-Tyne : North-East District Committee, Communist Party, 1943)
1943-10 1943 1940s 36 pages REPORT OF A CONFERENCE ON "The Health of the People" IN THE LECTURE HALL, NEWS THEATRE, PILGRIM STREET, NEWCASTLE-ON-TYNE, HELD SATURDAY, 9th OCTOBER, 1943. North-East District Committee, Communist Party, 2, Clayton Street, Newcastle-on-Tyne, 1. 15X/2/103/295